2017
DOI: 10.1016/j.ajo.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

The United Kingdom Diabetic Retinopathy Electronic Medical Record Users Group: Report 3: Baseline Retinopathy and Clinical Features Predict Progression of Diabetic Retinopathy

Abstract: PURPOSE To determine the time and risk factors for developing proliferative diabetic retinopathy (PDR) and vitreous hemorrhage (VH). DESIGN Multicenter, national cohort study. METHODS Anonymized data of 50 254 patient eyes with diabetes mellitus at 19 UK hospital eye services were extracted at the initial and follow-up visits between 2007 and 2014. Time to progression of PDR and VH were calculated with Cox regression after stratifying by baseline diabetic retinopathy (DR) severity and adjusting for age, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…Additionally, VB, IRMA, duration of diabetes, hypertension, logMAR vision, and arteriovenous nicking were determined as independent risk factors for NPDR progression to PDR after adjustment for age and sex, while the age of DM onset was determined as an independent protective factor, which was consistent with previous studies [ 19 , 23 26 ]. Furthermore, our results indicated that VB and IRMA were important predictors of NPDR progression to PDR, and the ORs of VB were even greater than that of IRMA.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Additionally, VB, IRMA, duration of diabetes, hypertension, logMAR vision, and arteriovenous nicking were determined as independent risk factors for NPDR progression to PDR after adjustment for age and sex, while the age of DM onset was determined as an independent protective factor, which was consistent with previous studies [ 19 , 23 26 ]. Furthermore, our results indicated that VB and IRMA were important predictors of NPDR progression to PDR, and the ORs of VB were even greater than that of IRMA.…”
Section: Discussionsupporting
confidence: 87%
“…Previous clinicopathologic study demonstrated that IRMA had the particular potential for neovascularization [ 18 ]. Recent study suggested that IRMA significantly increased risk of PDR [ 19 ]. Additionally, our study also contributed data regarding the prevalence of other retinal vascular lesions, including capillary nonperfusion, arteriovenous nicking, and DME, among different DR severity levels.…”
Section: Discussionmentioning
confidence: 99%
“…Such ''Big Data'' approaches have been successfully used to characterize the population and predict outcomes in other ophthalmic diseases. [11][12][13][14][15] This study aims to use largescale EMR data for comparing the rate of visual field (VF) loss in uveitis patients with glaucoma, compared to those with primary open-angle glaucoma (POAG), and explore whether this is associated with IOP.…”
mentioning
confidence: 99%
“…Instead, the regenerative activity of the retina results in the gradual reabsorption of some lesions, meaning that they can disappear from fundus photographs . Alternatively, microaneurysms may rupture, forming haemorrhages, which are significantly associated with the development of vitreous haemorrhages and diabetic macular oedema in later life .…”
Section: Lesion Dynamicsmentioning
confidence: 99%